2017
DOI: 10.1161/strokeaha.116.014068
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Blend Sign Is Associated With Computed Tomographic Angiography Spot Sign and Predicts Secondary Neurological Deterioration After Intracerebral Hemorrhage

Abstract: Background and Purpose-Significant early hematoma growth in patients with intracerebral hemorrhage is an independent predictor of poor functional outcome. Recently, the novel blend sign (BS) has been introduced as a new imaging sign for predicting hematoma growth in noncontrast computed tomography. Another parameter predicting increasing hematoma size is the well-established spot sign (SS) visible in computed tomographic angiography. We, therefore, aimed to clarify the association between established SS and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 13 publications
2
50
0
Order By: Relevance
“…Of the 275 patients with ICH, 47 had Blend Sign I (16.85%), consistent with the findings of Li et al (16.9%) [8] and Sporns et al (20.3% 37/182) [11]. However, only 17 patients had Blend Sign II (6.09%).…”
Section: Discussionsupporting
confidence: 86%
“…Of the 275 patients with ICH, 47 had Blend Sign I (16.85%), consistent with the findings of Li et al (16.9%) [8] and Sporns et al (20.3% 37/182) [11]. However, only 17 patients had Blend Sign II (6.09%).…”
Section: Discussionsupporting
confidence: 86%
“…The imaging sign HD was defined as any hypodense region strictly encapsulated within the hemorrhage with any shape, size, and density which does not require a density measurement [6,15,22]. The spot sign on CTA was well-acknowledged as the foci of enhancement within the intracranial hematoma, detected on CTA source images [23,24].…”
Section: Image Analysismentioning
confidence: 99%
“…The results of other studies [21] have suggested that CT variables indicating early hematoma expansion, such as spot sign on CTA, are the most reliable predictors of outcome. Also, a spot sign had a higher sensitivity for predicting outcome than did black hole sign in any location (34.6% vs. 23.1%) [22].…”
Section: Discussionmentioning
confidence: 89%
“…Early CT protocols in patients with ICH used only NCCT or CTA after NCCT for evaluation of critical imaging findings of ICH expansion [19]. Subsequent papers reported the relationship between imaging findings of CTA and NCCT and ICH expansion [20][21][22]. The study of Sporns et al [20] found that NCCT imaging markers were strongly correlated with an established spot sign.…”
Section: Discussionmentioning
confidence: 99%